2008
DOI: 10.1093/cvr/cvn290
|View full text |Cite
|
Sign up to set email alerts
|

Expression of skeletal but not cardiac Na+ channel isoform preserves normal conduction in a depolarized cardiac syncytium

Abstract: Expression of SkM1 but not Nav1.5 preserves AP upstroke and CV in a K(+)-depolarized syncytium. The higher AV and shorter excitable gap observed during reentry excitation around a void in SkM1 cultures would be expected to facilitate reentry self-termination. SkM1 Na(+) channel expression represents a novel gene therapy for the treatment of reentrant arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…In vitro studies indicated that overexpressing the cardiac Na + -channel (SCN5A) has only a minor effect on cardiac myocyte Na + -channel availability 35 because there is a large endogenous pool of Na + -channels whose availability is primarily limited by the kinetics of inactivation. Thus, overexpressing SCN5A should have only a minor effect on the AP threshold.…”
Section: Facilitating Diastolic Depolarization By Hyperpolarizing Ap mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies indicated that overexpressing the cardiac Na + -channel (SCN5A) has only a minor effect on cardiac myocyte Na + -channel availability 35 because there is a large endogenous pool of Na + -channels whose availability is primarily limited by the kinetics of inactivation. Thus, overexpressing SCN5A should have only a minor effect on the AP threshold.…”
Section: Facilitating Diastolic Depolarization By Hyperpolarizing Ap mentioning
confidence: 99%
“…In contrast, the skeletal muscle Na + -channel (SkM1) has inactivation kinetics 10-15 mV more positive than SCN5A. 35 Moreover, microelectrode recordings on isolated myocardial bundles showed that SkM1 overexpression hyperpolarizes the AP threshold potential ( Figure 3A). In the presence of an unchanged maximum diastolic potential, the net result was that membrane potential was now closer to threshold.…”
Section: Facilitating Diastolic Depolarization By Hyperpolarizing Ap mentioning
confidence: 99%
“…These cells express adenovirus and lentivirus carrying genes with high efficiency and also can be transfected with reasonable efficiency by electroporation. [38][39][40] This latter trait permits candidate genes to be prescreened for efficacy before a viral vector is prepared. The automaticity of these cultures derives in part from relatively low background potassium current (I K1 ).…”
Section: Establishing Proof Of Concept For Biological Pacingmentioning
confidence: 99%
“…In NBRV, SkM1 but not SCN5a is able to ''rescue'' the action potential upstroke from the depressing effect of potassium depolarization (10 mmol/L). 39 In the next section, we discuss the efficacy of SkM1 coexpressed with HCN2 in the canine heart as a biological pacemaker.…”
Section: Boink and Robinson 431mentioning
confidence: 99%
“…98 Together with gap-junctional modification, these studies begin to develop a novel toolkit for altering electric conduction by focal gene transfer.…”
Section: Cho and Marbánmentioning
confidence: 99%